2016
DOI: 10.1007/s00038-015-0778-4
|View full text |Cite
|
Sign up to set email alerts
|

Over-indebtedness and chronic disease: a linked register-based study of Finnish men and women during 1995–2010

Abstract: Over-indebtedness is associated with harmful health conditions. Policy makers should consider taking steps to prevent over-indebtedness and to increase the awareness of social and health service professionals of the problems associated with over-indebtedness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…Due to the cross-sectional nature of the present study, the causal direction of the observed association remains unclear. It is both possible that mental illness underlying antidepressant use results from over-indebtedness and mental illness contributes to over-indebtedness by reducing the capability to manage debt [11,6,7]. Furthermore, a broadly accepted definition of over-indebtedness is not yet available [1].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…Due to the cross-sectional nature of the present study, the causal direction of the observed association remains unclear. It is both possible that mental illness underlying antidepressant use results from over-indebtedness and mental illness contributes to over-indebtedness by reducing the capability to manage debt [11,6,7]. Furthermore, a broadly accepted definition of over-indebtedness is not yet available [1].…”
Section: Plos Onementioning
confidence: 99%
“…Besides physical morbidity, e.g. diabetes [7], obesity [8] and pain [9,10], over-indebtedness has consistently been found to be associated with mental illness, including psychoses [7] and depression [11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Studies found an association between over-indebtedness and poor health outcomes that was not explained by standard socioeconomic status (SES) measures such as income and education [7][8][9][10][11][12]. A 15-year longitudinal study among 48778 adults in Finland found an association between over-indebtedness and an increased incidence of various chronic diseases including diabetes and psychoses [13]. These findings suggest that overindebtedness may reflect a distinct risk factor of poor health.…”
Section: Introductionmentioning
confidence: 99%
“…Over-indebtedness, characterized by the inability to fulfill one's financial obligations, has been shown to be associated with both physical and mental health conditions [3], even including suicidal ideation [4] and completed suicide [1]. Other health hazards associated with over-indebtedness include obesity [5], pain [6,7], sleeping problems and sleep medication use [8], psychosis, diabetes [9], and poor adherence to prescribed medication [10].…”
Section: Introductionmentioning
confidence: 99%